Strategic analysis of the business of the enterprise - Nikolić Miloš; Stošić-Mihajlović Ljiljana (Trendovi u Poslovanju)
Modern business conditions are determined by uncertainty, rapid change and business in a dynamic and turbulent business environment. It is clear that the environment has an impact on the business of the enterprise, but the enterprise also has some influence on the environment. In this context, it is very important to conduct a strategic analysis of the environment that we divide into internal and external. External environment analysis refers to the analysis of opportunities and threats, while the internal analysis focuses on the analysis of the strengths and weaknesses of the company. In this paper the emphasis is placed on the most significant methods for strategic analysis of the businesses most commonly used in practice. By applying these methods, businesses come up with important environmental information that they need when formulating a business strategy. Adequate strategic analysis of the environment is the basis for successful business and survival of a company in the market